OPTIMIZING ADOBE EXPERIENCE MANAGER PERFORMANCE: A MULTIFACETED APPROACH TO ENHANCING USER EXPERIENCE AND SYSTEM EFFICIENCY - Bhanu Phanindra Babu Gogula (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a comprehensive framework for ensuring and optimizing application performance in Adobe Experience Manager (AEM), a widely-used content management system. As digital experiences become increasingly crucial for business success, the performance of AEM applications directly impacts user engagement, business continuity, and operational costs. This article examines key performance metrics, including response time, resource utilization, and user experience indicators, and explores advanced monitoring and assessment techniques. We propose a multifaceted optimization strategy encompassing front-end enhancements, back-end improvements, API call optimization, and effective heap memory management. Through case studies of e-commerce and content-heavy portal optimizations, we demonstrate the practical application and efficacy of these strategies. The article also addresses emerging challenges in AEM performance optimization and discusses the potential role of AI and machine learning in future performance management. By offering a systematic approach to continuous monitoring, measurement, and optimization, this study provides valuable insights for developers, system administrators, and business stakeholders seeking to maximize the performance and scalability of their AEM applications.